(3QSGdI aj Yde GddZI (B( (3aj MQaj GdUGO hGdVGO (B)s
(3ChdgG (B:s
(3CaVd eG jbGd Hg GdEfSGH hNjQ eG LQi Hg GddSGf MeOkG GdBdGg hGdUdGg hbQC HGdVGO Ydi ESJhGA s
(3BNQgG (B:s
(3Ke GdSHGY hGdPFGH YVJ hMQe Gddg GdQHG hMbQG MbQG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(505 (3O(B) s
Keywords: (3GdeLGejYs